Nurturing Micro, Small, and Medium Enterprises (MSMEs/UMKM): Unleashing the Power of Islamic Economic Innovation through a Historical Lens - Jailani, Mohammad; Alshahra, Mohammed Ali; H Alhassan, Muneera Fawaz; Lianti, Lia (Graduate School of UIN Syarif Hidayatullah Jakarta, 2023)
The focal point of this study lies in the impact of the Covid-19 pandemic on the economic landscape of Micro, Small, and Medium Enterprises (MSMEs) within the Yogyakarta community, particularly in the Kotagede area. Numerous MSMEs and local trade stalls have become non-operational due to the adverse effects of the pandemic, leading to financial distress and, in some cases, bankruptcy. This article addresses this issue within the context of Islamic economics by drawing insights from its foundational theories and proponents. The aim is to provide inspiration for MSMEs and entrepreneurs in Indonesia. The research employs a literature-based qualitative methodology, utilizing sources from Google Scholar, Scopus, and relevant books on Islamic economics, MSMEs, INOVASI, and Indonesian traders. The data analysis is conducted through a robust content analysis approach. The findings reveal an innovative model within Islamic economics that fosters creativity and initiative among MSMEs, particularly in Kotagede, Yogyakarta. Despite the intermission experienced by many small businesses during the pandemic, the encouragement for innovation from local authorities, including the Minister of Tourism and Culinary, has facilitated their return to business operations. Additionally, the study sheds light on the historical perspectives of Islamic economics by examining the contributions of experts such as Boediyono, Ibnu Khaldun, Abu Hanifa, and Zaid bin Ali. The implications of this research are significant in fortifying the Islamic economic sector, specifically for MSMEs in Indonesia.